Seed Coat Resistance of Groudnut to Aspergillus Flavus and Their Stability Performance in The Field - Kasno, Astanto; Trustinah, Trustinah; Purnomo, J.; Sumartini, Sumartini (AGRIVITA, Journal of Agricultural Science, 2011)
One of the weaknesses of the groundnut is the easiness to be infected by fungi, especially Aspergillus flavus that produces aflatoxin. Seed from the field experiments for all step of selection (F5 until to multilocation yield test) after processed then stored for 3 and 6 months, further tested their respons to A. flavus using a standard method. Examined for seed coat resistance to colonization of A. flavus were carried out in laboratory ILETRI (Indonesian of Legume and Tuber Crops Research Institute) since years of 2002 to 2006. Stability performance of resistance to A. flavus was analyzed with regression technique. Performance of resistance to A. flavus of selected lines tested were not consistant among 16 of testing envoronments. Among genotypes were also sigficantly different response to A. flavus invasion from location to location, indicated that those performance of some lines were not stable, except line of MHS/91278-99-C-180-5. The highest pod yield was occupied by line of J/91283-99-C-90-8 and stable, however its resistance to A. flavus did not stable. The resistance of J/91283-99-C-90-8 to A. flavus antil to three months after after seed strored similar with variety of J-11. Keywords: groundnut, Aspergillus flavus, aflatoxin